Analisis Efektivitas Penagihan Tunggakan Pajak Dengan Surat Paksa Dalam Rangka Meningkatkan Penerimaan Pajak Di KPP Pratama Jakarta Matraman Tahun 2019-2021 - Ferdiansyah Arista; Irawati Irawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research is motivated by the policy of Income Tax on E-Commerce Platform transactions that are developing in Indonesia must receive attention from the government. This is due to the large potential taxation of the online business.Do online business people on the e- commerce platform understand if the online transaction activities they are doing contain tax obligations? The tax treatment applied to online shop business people is exactly the same as the tax treatment of business people with conventional store models, namely income tax. The purpose of this study to evaluate the Income Tax Policy of online entrepreneurs on e-Commerce platform transactions in KPP Pratama Jakarta Koja. This study uses qualitative research methods. The Data used are primary data obtained from informant interviews and secondary data. Data collection technique is done by interview, observation, and documentation. The results showed that the evaluation of the Income Tax Policy of e-commerce platform entrepreneurs in KPP Pratama Jakarta Koja is very large, especially in Indonesia, but unfortunately there are no special regulations that actually regulate the taxation of Online transactions on E-Commerce platforms. In principle, there is no different tax treatment between an e-Commerce business and a conventional business. The suggestion in this research is that the Indonesian government can establish a special regulation related to the levy of online entrepreneur income tax on e-Commerce Platform transactions in order to exploit the great potential of the Indonesian people for the widespread use of online-based transactions better and orderly as a source of State Revenue